Análisis de la influencia de la precipitación en el esfuerzo de succión y la estabilidad de un talud - Valverde-Ruiz, Enrique Alonso (Instituto Tecnológico de Costa Rica, 2010)
Rain causes a change in soil moisture which in turn generates a change in the shear strength, including suction stress, also in soil’s parameters such as unit weight. These changes directly affect the stability of the slope. Information obtained in situ by instrumenting the slope was used in this study. Simultaneously, shear strength test were conducted to obtain analysis parameters. A rain forecast model used to evaluate the soil moisture change and their effect in the strength parameters was used. With this information, the analyses of stability using Fellenius and Bishop methods were made, considering a surcharge in the slope. Also, a probability of failure by using the Rosenblueth method was calculated. The influence of the precipitation has a direct impact on soil moisture. An increase in rain results in a decrease in suction stress which leads to a decrease in the slope safety factor and an increase in the probability of failure. The suction loss, which is not considered in conventional analysis, decreases approximately 8% the safety factor.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Suelo; Saturación; Falla; Muro; Contención